Development of Throttle Position Sensor Practical Trainer - Pahlevi, Reza Trio; Putra, Dwi Sudarno; Purwanto, Wawan; Setiawan, M Yasep (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2024)
The Throttle Position Sensor (TPS) is one of several sensors involved in electronic control technology in vehicle engines. This sensor is used to determine the throttle opening angle position. For automotive students, understanding how the TPS works is essential. Thus far, in learning about position angle sensors, the component used as a basis is a variable resistor/potentiometer. This component has limitations in terms of accuracy both in stimulus and sensor output. This research aims to develop a practical demonstration of a position angle sensor. The method used in this research is Research and Development (R&D). The research successfully created a demonstration of a position angle sensor with a range of rotation angles from 0° to 300°, with an accuracy of 98%. Throttle Position Sensor (TPS) merupakan satu dari beberapa sensor yang terlibat dalam teknologi pengontrolan elektronik pada mesin kendaraan. Sensor ini digunakan untuk mengetahui posisi sudut bukaan throttle. Bagi peserta didik bidang otomotif pemahaman pada cara kerja TPS menjadi salah satu hal penting. Selama ini dalam pembelajaran sensor posisi sudut komponen yang dijadikan dasar adalah variable resistor / potensiometer. Komponen ini memiliki kekurangan dalam hal akurasi baik pada sisi stimulus maupun output sensor. Penelitian ini bertujuan untuk mengembangkan sebuah peraga praktikum sensor posisi sudut. Metode yang digunakan dalam penelitian ini adalah Research and Development (R&D). Penelitian berhasil mewujudkan peraga sensor posisi dengan range sudut putar 0° hinga 300°. Dengan akurasi sebesar 98%.